Estimating the potential migration from Turkey to the European Union: A literature survey - Secil Pacaci Elitok (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The likelihood of a potential migration flow from Turkey into the European Union (EU) has increasingly been the focus of debates among academics and policy makers. As having one of the fastest growing populations of Europe, Turkey and its migration potential are the nexus of fears and concerns. Against this background, this paper is a survey of the growing literature on the estimations of the volume of potential migration from Turkey to the EU within the context of possible Turkish membership. Taking into account the methodological problems, drawbacks of the data and definitional issues, this article aims at critically evaluating the existing literature. In the light of potential migration discussions, this paper emphasizes the necessity of a shift in the focus of debate from quantitative aspects, that are overemphasizing the economic aspects, to qualitative dimensions of migration potential from Turkey to the EU.
Keywords: 330